Implementation of the Use of Daily Journals in PAUD Institutions - Amelia, Zahrina; Pansuri, Fitria Farhani (Edukasi, 2021)
One strategy to encourage children's early literacy skills, especially those aged 3-5 years, is to keep a daily journal so that children can communicate their thoughts, feelings and record their ideas through scribbles or pictures. Furthermore, scientific studies show that expressing what a person thinks and feels in a journal can have a positive impact on the author's physical and mental health. Based on the previous research, the researcher was interested in seeing how the "Implementation of the Use of Daily Journals in PAUD Institutions" using qualitative research methods and data collection methods using interviews and observations. The research was conducted in Jakarta and Depok, with a total number of respondents 12 teachers from four different kindergartens. The results showed that this daily journal was considered by most teachers to be able to support early literacy development even though the duration of work, writing equipment used and the form of support provided by teachers and parents are varied. In addition, most respondents also revealed that making daily journals can facilitate children to develop the ability to regulate their emotions in the morning, develop creativity, and help smooth daily teaching and learning activities. Therefore it can be say that a daily journal is a tool to expose children's social emotional problems, which always can help help to recognize and overcome the problems that faced with children, which can also help them to identify and overcome new problems, such as “new normal situation” when pandemi covid19 is over.